Combining Spin-Seebeck and Nernst Effects in Aligned MnBi/Bi Composites - Brandi L. Wooten; Koen Vandaele; Stephen R. Boona; Joseph P. Heremans (Nanomaterials, 2020)
The spin-Seebeck effect (SSE) is an advective transport process traditionally studied in bilayers composed of a ferromagnet (FM) and a non-magnetic metal (NM) with strong spin-orbit coupling. In a temperature gradient, the flux of magnons in the FM transfers spin-angular momentum to electrons in the NM, which by the inverse spin-Hall effect generates an SSE voltage. In contrast, the Nernst effect is a bulk transport phenomenon in homogeneous NMs or FMs. These effects share the same geometry, and we show here that they can be added to each other in a new combination of FM/NM composites where synthesis via in-field annealing results in the FM material (MnBi) forming aligned needles inside an NM matrix with strong spin-orbit coupling (SOC) (Bi). Through examination of the materials’ microstructural, magnetic, and transport properties, we searched for signs of enhanced transverse thermopower facilitated by an SSE contribution from MnBi adding to the Nernst effect in Bi. Our results indicate that these two signals are additive in samples with lower MnBi concentrations, suggesting a new way forward in the study of SSE composite materials.